Utricularietum australis Th. Müller et Görs 1960 in Poland - Krzysztof Spałek (Acta Societatis Botanicorum Poloniae, 2011)
The paper presents the distribution, floristic composition and ecological requirements of the pleustonic plant community Utricularietum australis Th. Müller et Görs 1960 in Poland. The association was classifield to the Lemnetea minoris class. Utricularietum australis is considered to be a rare and endangered plant community in Europe.